2021
DOI: 10.3390/ijms22084150
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide Induces the Acquisition of Invasive Phenotype by O6-Methylguanine-DNA Methyltransferase (MGMT)+ Glioblastoma Cells in a Snail-1/Cx43-Dependent Manner

Abstract: Glioblastoma multiforme (GBM) recurrences after temozolomide (TMZ) treatment result from the expansion of drug-resistant and potentially invasive GBM cells. This process is facilitated by O6-Methylguanine-DNA Methyltransferase (MGMT), which counteracts alkylating TMZ activity. We traced the expansion of invasive cell lineages under persistent chemotherapeutic stress in MGMTlow (U87) and MGMThigh (T98G) GBM populations to look into the mechanisms of TMZ-induced microevolution of GBM invasiveness. TMZ treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Despite numerous studies that have appointed Lyn as a key molecule of tumorigenesis, specific inhibitors for this kinase are still lacking. Several inhibitors can potently block the kinase activity of Lyn as part of a pan-SFK inhibition through their interaction with the catalytic domain, but all have wide spectra of additional targets, most likely due to the homolog of the fold of the kinase domain, which is similar to all other known protein kinases [ 3 , 4 ]. This can partially explain the limited efficacy of dasatinib in some tumor entities including glioblastoma, despite its high potency to induce tumor cell death [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous studies that have appointed Lyn as a key molecule of tumorigenesis, specific inhibitors for this kinase are still lacking. Several inhibitors can potently block the kinase activity of Lyn as part of a pan-SFK inhibition through their interaction with the catalytic domain, but all have wide spectra of additional targets, most likely due to the homolog of the fold of the kinase domain, which is similar to all other known protein kinases [ 3 , 4 ]. This can partially explain the limited efficacy of dasatinib in some tumor entities including glioblastoma, despite its high potency to induce tumor cell death [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, glioma cells surviving after therapy escape from the tumor to the parenchyma of a healthy human brain like living beings. It seems that the more intense and effective the therapy is, the higher the ability of surviving cells to migrate [ 16 , 17 , 18 ]. For example, Shimizu et al showed that bevacizumab therapy kills many tumor cells, but surviving cells have upregulation of δ-catenin expression, and it is associated with increased invasion of glioma cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Shimizu et al showed that bevacizumab therapy kills many tumor cells, but surviving cells have upregulation of δ-catenin expression, and it is associated with increased invasion of glioma cells [ 15 ]. Another study by Kochanowski et al showed that TMZ possibly enhances the invasiveness of surviving tumor cells and that this invasiveness correlates with upregulation of ectopic expression of Snail1 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…MGMT is expressed in both cell lines. However, this is much higher in T98G cells such that TMZ resistance is demonstrated, while only a low basal amount is observed in A172 [ 32 , 33 ]. In addition, in contrast to A172 cells, T98G cells express the S100 protein that functions as an intracellular Ca 2+ sensor, which contributes to tumorigenic processes and facilitates drug resistance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%